The Results of the Professional Preparation Project for Clinical Psychology Students: 4 Years Retrospective Study - Phungpong, Songsom; Kintarak, Sunisa (Journal of health and health management, 2020)
The Retrospective Study brought the data of clinical psychology program at Saint Louis College into statistical analysis. The study aimed to evaluate the results of a professional preparation project for clinical psychology students. The information was gathered from the extra-curricular program of 4 academic years, 2015-2018. The program prepared the students in terms of professional recognition, knowledge, and skills before participating their practicum or on-the-job-training. The results indicated that the preference of all 4 academic years students were in the very high level. The students highly obtained useful knowledge and professional experiences. In addition, the clinical supervisors at the training sites evaluated the students’ preparation and readiness and compared to clinical psychology students from other academic settings. Some domains of readiness and preparation were considered higher or better than the others. The supervisors pointed that 71.4 % of the students were qualified to become clinical psychologists in the future, while 28.6 % of the students were fairly accepted. In conclusion, the professional preparation project for clinical psychology students contributed positive and professional attitudes, which resulted commitment into the professional career path. Therefore, the program should be organized continuously along with the progressive concepts of coursework in order to produce competent and trustworthy graduates in clinical psychology.